Pengaruh Penggunaan APD Masker dengan Kejadian ISPA pada Pekerja Meubel di Desa Karduluk Tahun 2019 - Laylatul Hasanah (Wiraraja Medika : Jurnal Kesehatan, 2019)
Indonesia industrial keeps growing makes patterns a disease in people especially workers being changed, workers spend less more 8 hours day to work, the state of the environment place work has exposure and processes potential work potential an impairment of health meaning that can take one example in furniture.Karduluk village is with the number of people in sumenep districts largest furniture workers , based on the data from village heads karduluk that 80 percent of the people work in furniture , ranging from a worker as cutting timber up to painting , and based on the results of observation on 5 furniture 80 % of workers do not use a mask. The workers using a mask as the ari of respondents in furniture 48 in hamlet blajud karduluk village have the habit of wearing a mask as many as people 2 (100%) and suffered from complaints about the percentage of people with mild 2 100 % and no complaints of respondents who experienced heavy and the respondents who do not have the habit of wearing a mask as many as people 46 (100 %) and suffered from complaints about the mild 4 ( 8,69 % ) and suffered from complaints weigh as much as the 42 ( 91,30 % ). Method of Statistically the chi-square obtained using the p = 0,013 smaller than α ( 0,05 ). Means that there is the influence of the wearing a mask as the ari, making it necessary to issue regulations on the use of masks.